2021
DOI: 10.1155/2021/4579850
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology-Based Study on Irritable Bowel Syndrome Prevention and Treatment Utilizing Shenling Baizhu Powder

Abstract: Background and Objective. Irritable bowel syndrome (IBS) is a prevalent disorder of the gastrointestinal system with complex pathogenesis. Shenling Baizhu powder (SLBZP) is a Chinese herbal compound with multicomponent and multitarget characteristics. Increasing volumes of evidence demonstrate that it has a notable therapeutic impact on IBS. This study therefore is aimed at exploring the potential effective components of SLBZP and their mechanisms in IBS treatment utilizing network pharmacology. Methods. Metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Conditions associated with ACHE include colonic pseudo-obstruction. With deepening understanding of the brain-gut axis in the pathogenesis of IBS [34], more attention should be paid to the role of ACHE in IBS [35]. Te present study detected a signifcant increase in ACHE level in the IBS model in comparison to the control group, but interestingly, it was decreased after implementing 14 days of TXYF treatment.…”
Section: Discussionmentioning
confidence: 38%
“…Conditions associated with ACHE include colonic pseudo-obstruction. With deepening understanding of the brain-gut axis in the pathogenesis of IBS [34], more attention should be paid to the role of ACHE in IBS [35]. Te present study detected a signifcant increase in ACHE level in the IBS model in comparison to the control group, but interestingly, it was decreased after implementing 14 days of TXYF treatment.…”
Section: Discussionmentioning
confidence: 38%
“…[ 28 , 29 ] Some studies have shown that there is a certain imbalance of TNF in patients with IBS-D, which shows a manifestation similar to the inflammatory response, and it is feasible to effectively treat IBS-D by exerting anti-inflammatory effects through the TNF signaling pathway. [ 30 , 31 ] TP53, also known as the P53 gene, is an effective cancer inhibitor gene in the human body, playing the role of “gene guardian,” regulating the cell division process, assisting in cell repair, and there is a significant negative correlation between its expression and IL-6 protein, [ 32 ] while IL-6 belongs to the interleukin family, which is a glycosylated protein composed of 184 amino acids, an important inflammatory response factor, and plays an important regulatory function in infections. [ 33 ] One hundred eighty-four amino acids, is an important inflammatory response factor, and plays an important regulatory function in infection, some studies have found that patients suffering from irritable bowel syndrome have higher levels of IL-6 than the normal group on average, [ 34 ] and the changes in the level of inflammatory factors have a close relationship with the occurrence and development of IBS-D, so the level of IL-6 expression is often used as an indicator to monitor and judge the condition of IBS-D. [ 35 ] IL-1B is associated with pain, inflammation, and autoimmunity of the body, and is closely related to the cellular defense and tissue repair of the tissues, and it has been found that the level of IL-1B in the colonic mucosa and blood in IBS-D patients is higher than that in normals, which may be involved in the pathogenesis of IBS-D through the function of the organism’s colon.…”
Section: Discussionmentioning
confidence: 99%
“…The use of long-acting GnRH in the treatment of children with true precocious puberty may have a transient excitation response, which can promote the release of gonadotropin, so it can stimulate the desensitization of the pituitary gland and the feedback downregulation effect (26). The comprehensive result is to reduce the Targets level of gonadotropin, and the synthesis and effect of sex hormone.…”
Section: Discussionmentioning
confidence: 99%